Russian Trade and Foreign Direct Investment Policy at the Crossroads - Tarr, David; Volchkova, Natalya (2012)
This paper summarizes the estimates of what Russia will get from World Trade Organization accession and why. A key finding is the estimate that Russia will gain about $53 billion per year in the medium term from World Trade Organization accession and $177 billion per year in the long term, due largely to its own commitments to reform its own business services sectors. The paper summarizes the principal reform commitments that Russia has undertaken as part of its World Trade Organization accession negotiations, and compares them with those of other countries that have acceded to the World Trade Organization. It finds that the Russian commitments represent a liberal offer to the members of the World Trade Organization for admission, but they are typical of other transition countries that have acceded to the World Trade Organization. The authors discuss the outstanding issues in the Russian World Trade Organizaiton accession negotiations, and explain why Russian accession will result in the elimination of the Jackson-Vanik Amendment against Russia. They discuss Russian policies to attract foreign direct investment, including an assessment of the impact of the 2008 law on strategic sectors and the increased role of the state in the economy. Finally, the authors assess the importance of Russian accession to Russia and to the international trading community, and suggestions for most efficiently meeting the government s diversification objective.